Weaving Lao Silk Into Indigo Nights - Melody Kemp (Asia-Pacific Journal, 2010)
The air turned chilly as the sun sighed into the nearby hills. It picked up the smells of dust mixed with metallic and dung flavours. Miss Phaeng watched, holding her breath as the last sliver of red fell out of sight. Casting a quick mantra to the spirits of nature, she swallowed a glass of lao lao to start the evening.Leaning mindfully over her loom, Miss Phaeng raked her nails across the piano strings of silk warp, plucking each to test its tension. A black sheet of pin-straight hair fell over her face, hiding the claret birthmark shaped just like a spider, that crept over her right cheek, one leg disappearing into the fine hairs of her temple.The coarse ivory silk recently spooled from the cocoons gathered in her garden pushed back against her hand.She felt the fizz of anticipation low in her belly as she gathered all the many shuttles holding the weft silk and dumped them into an old blackened basket. Inhaling its heady stink of ash, grass and smoke, she placed the basket next to where she would sit.Melody Kemp offers a close look at the Lao silk industry.